Ventricular flow dynamics with varying LVAD inflow cannula lengths: In-silico evaluation in a multiscale model. (27th April 2018) - Liao, Sam; Neidlin, Michael; Li, Zhiyong; Simpson, Benjamin; Gregory, Shaun D.
Abstract: Left ventricular assist devices are associated with thromboembolic events, which are potentially caused by altered intraventricular flow. Due to patient variability, differences in apical wall thickness affects cannula insertion lengths, potentially promoting unfavourable intraventricular flow patterns which are thought to be correlated to the risk of thrombosis. This study aimed to present a 3D multiscale computational fluid dynamic model of the left ventricle (LV) developed using a commercial software, Ansys, and evaluate the risk of thrombosis with varying inflow cannula insertion lengths in a severely dilated LV. Based on a HeartWare HVAD inflow cannula, insertion lengths of 5, 19, 24 and 50 mm represented cases of apical hypertrophy, typical ranges of apical thicknesses and an experimental length, respectively. The risk of thrombosis was evaluated based on blood washout, residence time, instantaneous blood stagnation and a pulsatility index. By introducing fresh blood to displace pre-existing blood in the LV, after 5 cardiac cycles, 46.7%, 45.7%, 45.1% and 41.8% of pre-existing blood remained for insertion lengths of 5, 19, 24 and 50 mm, respectively. Compared to the 50 mm insertion, blood residence time was at least 9%, 7% and 6% higher with the 5, 19 and 24 mm insertion lengths, respectively. No instantaneous stagnation at the apex was observed directly after the E-wave. Pulsatility indices adjacent to the cannula increased with shorter insertion lengths. For the specific scenario studied, a longer insertion length, relative to LV size, may be advantageous to minimise thrombosis by increasing LV washout and reducing blood residence time.